The predictability of exchange rates using oil price changes : a thesis presented in partial fulfilment of the requirements for the degree of Master of Management in Finance at Massey University - Cui, Yingyao (Massey University, 2005)
This study investigates the predictability of exchange rates using oil price changes. It is found that, on a daily basis, changes in oil prices predict several major currency exchange rate returns. In the twenty-three year sample of daily data for currency markets, a statistically significant predictability is found for the Australian Dollar, the Canadian Dollar, the British Pound, the Norwegian Krone and the New Zealand dollar. These currencies appreciate when oil price increases, and vice versa. While I do reject the random walk model for currency returns, my results do not necessarily imply a rejection of market efficiency. Key words: Foreign exchange rate, oil price.
Keywords: Foreign exchange rates; Econometric models; Petroleum products -- Prices; Oil price